IABSE Conference, Rotterdam 2013: Assessment, Upgrading and Refurbishment of Infrastructures 2013
DOI: 10.2749/222137813806479124
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Reliability Assessment of Industrial Heritage Bridges

Abstract: Prof., involved in reliability analyses and risk assessments of structures. Summary Methods for reliability assessment of bridges registered as industrial heritage are developed taking into account principles of EN 1990, ISO 13822 and ISO 2394. A proposed probabilistic procedure allows for consideration of new information obtained from inspections or monitoring and satisfactory past performance. Application of general principles is illustrated in the assessment of a reinforced concrete road bridge. The study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The verification considering the partial factors recommended in Eurocodes [35] revealed that actual resistance is 10% lower than that that required to comply with design requirements (common situation of existing bridges designed according to past standards). This leads to BMSP = 0 (SL = 0%, high EI new ).…”
Section: Example 1-remaining Service Life Of An Existing Bridgementioning
confidence: 99%
See 3 more Smart Citations
“…The verification considering the partial factors recommended in Eurocodes [35] revealed that actual resistance is 10% lower than that that required to comply with design requirements (common situation of existing bridges designed according to past standards). This leads to BMSP = 0 (SL = 0%, high EI new ).…”
Section: Example 1-remaining Service Life Of An Existing Bridgementioning
confidence: 99%
“…Reliability assessment should verify whether or not the bridge can remain in service for the next 25 years; considering a target reliability index of 3.1. The reliability assessment of the slab was analysed [35]-the main outcomes of this analysis are applied in the following sustainability assessment. The focus is on ULS.…”
Section: Example 1-remaining Service Life Of An Existing Bridgementioning
confidence: 99%
See 2 more Smart Citations
“…An important step in any reliability analysis is the specification of probabilistic models for the basic variables. The probabilistic models of resistance parameters and actions are based on the JCSS Probabilistic Model Code [13], following here simplifications adopted in [7,8] to provide generic models. The models are normalised by characteristic values of the basic variables (Table 1).…”
Section: Probabilistic Analysis -Case Studymentioning
confidence: 99%